Pregnancy outcome of a patient following myomectomy performed during first trimester for red degeneration of fibroid (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Pain due to red degeneration of fibroid during pregnancy is usually associated with large myomas. Necrobiosis / red degeneration typically manifests itself about midpregnancy when Lhe leiomyoma suddenly becomes acutely painful, enlarged and tender. The common differential diagnosis of this condition are torsion of the pedicle of an ovarian cyst/a leiomyoma, abruplion placentae, acute pyelitis or any abdominal catastrophe. Ultrasound can easily delineate the presence of myomas of mixed echogenicity along with pregnancy and clinical findings usually suggest the diagnosis of pregnancy complicated by red degeneration of fibroid. The acute pain usually subsides within 3-10 days of conservative treatment. Only refractory cases (2% of patients) may demand surgical intervention in early gestation with the known risk of miscarriage. Here we report a pregnancy managed at 13 weeks by myomectomy for red degeneration. The patient ultimately delivered a healthy female child at 38 weeks by lower segment caesarean section.